Protective Effect of Denosumab on Bone in Older Women with Primary Hyperparathyroidism. Issue 3 (24th January 2018) - Eller‐Vainicher, Cristina; Palmieri, Serena; Cairoli, Elisa; Goggi, Giovanni; Scillitani, Alfredo; Arosio, Maura; Falchetti, Alberto; Chiodini, Iacopo
Abstract : Objectives: To determine the effect of denosumab, which is used in primary osteoporosis (PO), in primary hyperparathyroidism (PHPT)‐related osteoporosis. Design: Retrospective, longitudinal study. Setting: Outpatient osteoporosis clinic. Participants: Older women with PHPT (78.6 ± 5.5) (n = 25) and PO (78.8 ± 5.2) (n = 25) matched on age, body mass index, familial history of hip fracture, femoral bone mineral density (BMD), and personal history of fragility fractures. Intervention: Twenty‐four months of denosumab therapy. Measurements: We assessed the calcium‐phosphorus metabolism parameters; BMD at the lumbar spine (LS), femoral neck (FN), and total hip (TH) using dual X‐ray absorptiometry; and morphometric vertebral fractures using radiographs in all subjects at baseline and after 24 months. Changes in BMD and total alkaline phosphatase (ALP) activity were considered significant if they were greater than the least significant change (LS 2.8%, FN 5.9%, TH 4.8%, ALP –22%) and were expressed as percentage difference between end of follow‐up and baseline (Δ). Results: After 24 months, women with PHPT had greater ΔALP (−30.6 ± 11.3), ΔFN (5.6 ± 4.8), and ΔTH (4.8 ± 4.4) than those with PO (ΔALP −21.4 ± 13.1, ΔFN 2.9 ± 4.8, ΔTH 1.2 ± 4.1, P  < .05 for all comparisons). A significant increase in BMD was more frequent in women with PHPT (92%) than in those with PO (52%, P  < .05) and it was 13.4 times as likely in women with PHPT as in those with PO ( P  = .02), regardless of possible confounders. Two subjects in each group had an incident fracture. Conclusions: Denosumab therapy is effective in older women with PHPT‐related osteoporosis.